Sự thuận cả hai tay về bán hàng và dịch vụ của nhân viên kinh doanh trong ngành dược phẩm B2B - Võ Thanh , Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper has developed a theoretical framework to explore the two components of ambidexterity (sales and service) or SSA, two groups of antecedent variables which are “reason to” motivation and the preference for structuring time of employees, two groups of outcome variables are job performance and roles response. This is the first study in Vietnam on SSA. The PLS-SEM approach was used to test the research model with survey data collected from 302 sales staffs in the B2B pharmaceutical company. Research results show that the impact of motivation, enjoyment work and polychronicity on SSA and the results will affect sales performance and creativity. The research findings provide policy implications for pharmaceutical company boards as well as managers.